ANALISIS KEMAMPUAN PEMAHAMAN KONSEP FISIKA TERHADAP MINAT DAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI USAHA DAN ENERGI KELAS X DI SMA NEGERI 6 PONTIANAK - Nur Eliza; Edy Tandililing; Muhammad Musa Syarif Hidayatullah (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2022)
The purpose of this study was to determine the ability to understand the concept of physics, the relationship between interest in learning and understanding the concept, the relationship between learning motivation and understanding the concept, and the relationship between interest and motivation to learn with the ability to understand the concept of physics in class X MIPA 1 SMA Negeri 6 Pontianak. The form of research used is correlational with a quantitative approach. The results showed that the ability to understand the physics concept of work and energy was an average percentage of 43% category less than once. The highest indicator of students' concept understanding is translation with a percentage of 61% in the sufficient category, while the lowest indicator of concept understanding is extrapolation with a percentage of 27.5% category less than once. In this study, there is a relationship between interest in learning and understanding of physics concepts of 0.399 which is at the level of a weak relationship. In addition, there is a relationship between learning motivation and understanding of physics concepts of 0.440 at the moderate level of relationship. Then there is a relationship between interest and motivation to learn with understanding the concept of physics of 0.505 which is at the moderate level of relationship. The results of this study are expected to be taken into consideration in determining learning strategies to improve students' conceptual understanding skills and increase students' interest and motivation to learn.